The Attitudes of Student-teachers toward Moodle as a Supplementary Learning Platform - Suparjan, -; Purwanta, Edi; Septiarti, Serafin Wisni; Purnomo, Yoppy Wahyu (JOIV : International Journal on Informatics Visualization, 2024)
During the COVID-19 pandemic, Moodle (Modular Object-Oriented Dynamic Learning Environment) emerged as a leading online learning platform, providing essential support for educational institutions transitioning to remote learning. However, its role as a supplementary tool alongside traditional teaching methods in non-pandemic contexts remains underexplored in academic research. This study aims to investigate the attitudes of higher education student-teachers toward Moodle as an asynchronous online learning platform that enhances traditional classroom learning. The research employed a descriptive-quantitative method, focusing on students from the Teacher Training and Education Faculty, specifically those in the Elementary School Teacher Education Department at Universitas Tanjungpura, Indonesia. Participants were selected through purposive sampling, targeting individuals with experience using Moodle in online and offline learning environments. Data were collected using a structured questionnaire to assess student-teacher attitudes toward Moodle. It underwent a rigorous validation process to ensure the instrument's validity, including expert reviews. The reliability of the questionnaire was assessed through a pilot test conducted with 25 elementary school student-teachers from a state university. The results indicate that most student-teachers have positive attitudes toward Moodle, particularly valuing its effectiveness in enhancing their traditional learning experiences. Despite these favorable views, further research is necessary to develop a more comprehensive understanding of Moodle as a learning management system. Future studies should explore a broader range of educational contexts and levels to better understand the diverse challenges and benefits of applying Moodle in different teaching environments.